Facile synthesis of multifunctional Fe3O4@SiO2@Au magneto-plasmonic nanoparticles for MR/CT dual imaging and photothermal therapy. Issue 31 (29th March 2017) - Hou, Xuemei; Wang, Xuandong; Liu, Rong; Zhang, Huicong; Liu, Xiaolong; Zhang, Yun
Abstract : Monodispersed and well-defined Fe3 O4 @SiO2 @Au magneto-plasmonic nanoparticles were synthesized by a facile method. They were demonstrated to be excellent MR/CT dual imaging and photothermal therapy theranostic agents. Abstract : Magneto-plasmonic nanoparticles have exhibited great potential in cancer diagnosis and therapy because of their excellent magnetic and optically activable plasmonic properties. However, it is still a great challenge to combine these two components in one single-nanoparticle. In this work, we developed a facile method to synthesize monodispersed and uniform theranostic agents of Fe3 O4 @SiO2 @GNSs–PEG (PMGNSs) nanoparticles. The as-synthesized PMGNSs composed of a superparamagnetic Fe3 O4 inner core, silica as the midlayer and coated with gold nanoshells at the outside, with uniform size distribution of less than 100 nm. It has been demonstrated to be with excellent magnetic resonance (MR) and computed tomography (CT) imaging contrast abilities at different concentrations. Meanwhile, the as-synthesized PMGNSs exhibited high stability with no significant change of photothermal performance after five laser ON/OFF cycles, and high photothermal conversion ability with temperature increase of 40 °C under 808 nm laser irradiation at 2 W cm −2 for 10 min at the concentration of 160 μg ml −1 . Furthermore, in vitro photothermal therapy ability has also been demonstrated on HePG2 cancer cells.